Microstructured Blood Vessel Surrogates Reveal Structural Tropism of Motile Malaria Parasites. Issue 6 (24th January 2017) - Muthinja, Mendi J.; Ripp, Johanna; Hellmann, Janina K.; Haraszti, Tamas; Dahan, Noa; Lemgruber, Leandro; Battista, Anna; Schütz, Lucas; Fackler, Oliver T.; Schwarz, Ulrich S.; Spatz, Joachim P.; Frischknecht, Friedrich
Abstract : Plasmodium sporozoites, the highly motile forms of the malaria parasite, are transmitted naturally by mosquitoes and traverse the skin to find, associate with, and enter blood capillaries. Research aimed at understanding how sporozoites select blood vessels is hampered by the lack of a suitable experimental system. Arrays of uniform cylindrical pillars can be used to study small cells moving in controlled environments. Here, an array system displaying a variety of pillars with different diameters and shapes is developed in order to investigate how Plasmodium sporozoites associate to the pillars as blood vessel surrogates. Investigating the association of sporozoites to pillars in arrays displaying pillars of different diameters reveals that the crescent‐shaped parasites prefer to associate with and migrate around pillars with a similar curvature. This suggests that after transmission by a mosquito, malaria parasites may use a structural tropism to recognize blood capillaries in the dermis in order to gain access to the blood stream. Abstract : Motile malaria parasites are investigated in a series of mixed micropillar arrays. Parasites are found to preferentially associate with the outside of pillars that mimick the curvature of blood vessels. This shows the general utility of mixed pillar arrays for the investigation of motile cells in their environment.